Taxonomy of Brazilian Psychoda Latreille, 1796 (Diptera, Psychodidae) with the description of thirteen new species - Cordeiro, Danilo; Bravo, Freddy; de Carvalho, Claudio J. B. (Zootaxa, 2011)
Thirteen new species of Brazilian Psychoda Latreille are described. Psychoda buxoides Quate, Psychoda laticaula Quate, Psychoda litotes Quate and Psychoda talamanca Quate are redescribed and illustrated. Also, the female of Psychoda dantilandensis Bravo, Cordeiro & Chagas is described for the first time, and additional characters are presented for Psychoda alternata Say, Psychoda alternicula Quate, Psychoda amazonensis Cordeiro & Bravo, Psychoda dantilandensis, Psychoda divaricata Duckhouse, Psychoda serraorobonensis Bravo, Cordeiro & Chagas, Psychoda savaiiensis Edwards, and Psychoda zetoscota Quate. Two identification keys for the species that occur in Brazil are also presented, one for males, one for females.